Thermal Profile of a Carpathian Cold-Air Pool: Teșnița Valley from Dorna Depression - Lucian SFÎCĂ; Andrei BÂRLEA; Pavel ICHIM; Robert HRIȚAC (Aerul şi Apa: Componente ale Mediului)
The present paper explores the thermal environment close to Poiana Stampei weather station using hourly data, collected during one full calendar year. The data was gathered by using professional air temperature data logger installed in a standardized weather shelter in the Teșnița Valley, located 1.2 km east from the official weather station, at 885 m. The monitored area is subject of strong air temperature inversions, which constitute the main explanation for an annual air temperature of 6.7°C, 1°C lower than at the nearby official weather station. This cold-air pool reached at hourly level an intensity of 11.7°C, which is impressive for an altitudinal difference of only 32 m. A description of the features of this cold-air pool is presented based on these in-situ measurements and also using some relevant mobile measurements during specific synoptic conditions. Moreover, synoptic conditions favorable for the cold-air development were also analyzed.